Expanding the histopathological spectrum of CFL2‐related myopathies. Issue 6 (25th March 2018) - Fattori, F.; Fiorillo, C.; Rodolico, C.; Tasca, G.; Verardo, M.; Bellacchio, E.; Pizzi, S.; Ciolfi, A.; Fagiolari, G.; Lupica, A.; Broda, P.; Pedemonte, M.; et al.
Abstract : Congenital myopathies (CMs) caused by mutation in cofilin‐2 gene ( CFL2 ) show phenotypic heterogeneity ranging from early‐onset and rapid progressive forms to milder myopathy. Muscle histology is also heterogeneous showing rods and/or myofibrillar changes. Here, we report on three new cases, from two unrelated families, of severe CM related to novel homozygous or compound heterozygous loss‐of‐function mutations in CFL2 . Peculiar histopathological changes showed nemaline bodies and thin filaments accumulations together to myofibrillar changes, which were evocative of the muscle findings observed in Cfl2 −/− knockout mouse model. Abstract :